A new species of Aktedrilus (Oligochaeta, Tubificidae) from the North Sea Coast of the Federal Republic of Germany - Erséus, C.; Kossmagk-Stephan, K.J. (Zool. Anz., Jena, 1982)
Aktedrilus sphaeropenis n. sp. is described from six sandy beaches of the island of Sylt. It is distinguished from other species of Aktedrilus Knollner, 1935 by the morphology of its penes (spherical, non-cuticularized), its spermatheca (ectal part of duct heavily muscular), and its posterior prostate glands (no broad attachements to penial sacs). In all but one beach the new species co-occurs with A. monospermathecus Knollner, 1935, but it is found in the middle-to-upper parts of the intertidal, whereas A. monospermathecus occurs in the lower parts.